Role of β(3) adrenoceptor in rat thoracic aorta contractility - Zhao, Qianqian (Int J Clin Exp Pathol, 2017)
To clarify the role of β(3)-AR in rat thoracic aorta contractility and underlying mechanisms. BRL 37344 (BRL) was used to detect the role of β(3)-AR on rat thoracic aorta. 40 rats were randomly divided into Sham control group, Sham+SR group with SR 59230A (SR) injected, chronic heart failure (CHF) control group, and CHF+SR group. The effects of SR on thoracic aorta structure, function and NF-κB expression were estimated. BRL produced relaxant effect in both endothelium-intact and endothelium-free aorta rings, which was antagonized by SR and partially by L-NAME, but not changed by Propranolol. Similar results were obtained on thoracic aorta smooth muscle of CHF rats. β(3)-AR was located in both vascular smooth muscle layer and endothelial layer. After SR injection, the aorta rings in Sham+SR group showed reduced endothelium-dependent relaxation response to Ach compared with Sham control group. The aorta rings in CHF control group showed reduced endothelium-dependent relaxation to Ach, with increased endothelium-dependent relaxation in CHF+SR group. Besides, SR injection showed increased contraction to NA. Meanwhile, NF-κB expression in Sham+SR group was higher than Sham control group, with increased expression in CHF control group but decreased in CHF+SR group. Microarray screening showed 48 and 42 differentially expressed miRNAs in Sham+SR rats and CHF+SR rats respectively with 19 of them associated with NF-κB pathways. β(3)-AR is expressed in rat aorta and exerts relaxant effects through NOS-dependent pathway. β(3)-AR Inhibition delayed damage of vessels in development of heart failure possibly through regulation of NF-κB signaling pathway.